Antihyperlipidemic activity of kaffir lime leaf extract (Citrus hystrix DC) on hypercholesterolemic model mice - Anjani, Ade Giriayu; Rosa Juwita Hesturini (Published by Universitas Gadjah Mada, 2025)
Kaffir lime (Citrus hystrix DC) is rich in various bioactive substances like flavonoids, tannins, saponins, hesperidin, and several monoterpenes, which are believed to have antihyperlipidemic activity. Hyperlipidemia is a metabolic issue that can lead to high blood pressure and weight gain. This condition is the result of an imbalance in cholesterol levels, including total cholesterol, elevated LDL, and reduced HDL. This study aimed to investigate the antihyperlipidemic activity of kaffir lime leaf extract (C. hystrix DC) on hypercholesterolemic model mice. It was pre- and post-control group design study. Tweenty-five male mice (Mus musculus) weighing 16-21g at 12 wk of age were used in this study. Five mice as normal control mice group (Group 1) were only administered 1% CMC-Na solution and 20 mice were administered an atherogenic diet to induce hyperlipidemic model. The hyperlipidemic mice were then randomly divided into four groups i.e. positive control mice group (Group 2) were administered simvastatin suspendet in 1% CMC-Na at dose of 0.03 mg/g BW, treatment mice group (Group 3-5) were administered C. hystrix DC leaf extract suspendet in 1% CMC-Na at doses of 0.21; 0.28; and 0.35 mg/g BW, respectively. The interventions were administered one daily for 14 d. Blood sampling from the retroorbital plexus of the mice was conducted before and 14 d after the intervention for lipid profile analysis. The serum total cholesterol, LDL, HDL, and triglyceride levels were measured by the CHOD-PAP (cholesterol oxidase-phenyl amino phyrazolone) enzymatic method. A significant decrease in total cholesterol, LDL, triglycerides levels, and a significant increase in the HDL level were observed in the treatment group at doses of 0.28; 0.35 mg/g BW compared to the normal control group (p<0.05). The maximal antihyperlipidemic activity was observed at dose of 0.28 mg/g BW. In conclusion, the C. hystrix DC leaf extract has antihyperlipidemic model mice.